Pola Makan, Aktivitas Fisik Terhadap Kejadian Obesitas Pada Guru Sma Dan Smk Di Kecamatan Tomohon Tengah Kota Tomohon - Daniel Robert; Meildy E Pascoal; Damaris C Kaunang (Jurnal GIZIDO, 2018)
Diet is a way or business in setting the number and types of food with a specific purpose such as maintaining health, nutritional status, medium enterprises or help cure diseases. The wrong diet can cause many significant on the health of the body. To maintain the health of the body eating habits must be noted by the teacher. Bad habits of diet foods high in energy and fat common cause of obesity. Based on the background of the researchers want to know whether the diet physical activity can cause obesity first on teachers. The type of research that is used is a research cohort studies analytically using the design of the cross sectional research study or cut the bars of 43 samples. Data Collection intake pattern is done by using the questionnaire Food Frequency Questioner (FFQ). Physical Aktivatas done by using questionnaires international pisycal activity quesionery (IPAQ) , and nutritional status is done using anthropometric measurement height measured using microtois and body weight is measured using body weight. Research Results diet includes the types of food, frequency eat using test chi-square test shows there are significant relationships between the amount of energy intake (p=0,000), the amount of protein intake (p=0,000), the amount of fat intake (p=0,000), the amount of carbohydrate intake (p=0,000), and from the results of the test the fisher exact test shows that there is no relationship between physical activity and nutritional status values (p=0.511).